The Impact of Family-Centered Prevention on Self-Regulation and Subsequent Long-Term Risk in Emerging Adults - Stormshak, Elizabeth (Prev Sci, 2018)
Emerging adulthood is characterized by opportunity and transition, but also a substantial increase in risk behaviors (Fosco, Caruthers, & Dishion, 2012; Johnston, O’Malley, Bachman, Schulenberg, & Miech, 2016). Building on prior research, we tested a mediational model hypothesizing that Family Check-Up (FCU) intervention effects on young adult risk would be mediated by increases in self-regulation, and that these changes would continue to affect risk behavior as high school youths transitioned to young adulthood. We also predicted that the intent-to-treat intervention would be associated with lower levels of risk in young adulthood and that this effect would be accounted for by intervention-induced improvements in self-regulation during early adolescence, which in turn would prevent young adult risk. Participants were 593 adolescents and their families recruited from three public middle schools and randomized either to the FCU or to a control group. Item response theory was applied to construct a measure of high-risk behavior at this age, including risk behaviors such as substance abuse, high-risk sexual behavior, and vocational risk. Results suggested that changes in children’s self-regulation that occurred early during the middle school years, and that were associated with the FCU, led to reductions in risk behaviors during young adulthood. This study builds on our prior research that has suggested that effects of the FCU during middle school lead to changes in a range of risk behaviors during the transition to high school (Fosco, Frank, Stormshak, & Dishion, 2013; Stormshak, Fosco, & Dishion, 2010).